HIPPOCAMPUS CELL DISORDERS AND NEUROSENSORY TESTS IN MICE (Mus musculus) DUE TO INDUCTION OF EXCESS SODIUM CHLORIDE - Cahyaningrum, Putri; Windusari, Yuanita; Setiawan, Arum (BIOVALENTIA: Biological Research Journal, 2021)
Salt or sodium chloride (NaCl) is an additive to give food a salty taste. The use of salt in everyday life is difficult to avoid. Salt has both good and bad effects on the body. The electrolyte content of salt can help launch metabolism in the body, whereas if the body contains too much salt it will cause heart attacks and hypertension. The dose of salt consumption that has been set by the government is 5g/day. This study was conducted to examine the effect of consuming excessive sodium chloride (NaCl) on the ability to smell and to what extent it damages cells in the hippocampus of mice (Mus musculus). The method of this study was CRD (completely randomized design) with 6 replications, 1 group control and 3 repetitions induced by sodium chloride (NaCl) is 260mg/gBB (P1), 520mg/gBB (P2), and 780mg/gBB (P3). The parameters of this study are neurosensory coordination in the form of olfactory response of mice (Mus musculus) to ammonia and cell disruption in the hippocampus (DG & CA) which were observed by histological preparations of Hematoxylin eosin (HE) staining. The results of this study indicate the presence of olfactory disorders in mice (Mus musculus) and cell death in the hippocampus also increased due to excessive sodium chloride (NaCl) induction. The more salt is consumed in daily life, it will disrupt the cells in the hippocampus.